1996
DOI: 10.1515/mamm.1996.60.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypes of two endemic species of hare from Ethiopia, Lepus habessinicus and L. starcki (Lagomorpha, Leporidae). A comparison with L. europaeus

Abstract: Karyotypes of two endemic species of hare from Ethiopia, Lepus habessinicus and L. starcki were studied and compared to that of L. europaeus. L. starcki has a fragmented range in the high Ethiopian plateaus and is considered a relict form of L. europaeus. In contrast, L. habessinicus occurs at lower altitudes, and is an arid-country species. The species share a 2n = 48 and a FNa = 88 common to all representatives of the genus. No sign of karyotypic differentiation is evident from G-banding and Ag-NOR location.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Previous studies have suggested that Lepus experienced rapid radiation [67,68]. The lack of chromosomal structural changes supports such a model of relatively recent, and rapid, diversification in this clade [69,70]. Low levels of genetic diversification between species could result in relatively fertile F 1 hybrids providing a bridge for further hybridization and thus introgression.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have suggested that Lepus experienced rapid radiation [67,68]. The lack of chromosomal structural changes supports such a model of relatively recent, and rapid, diversification in this clade [69,70]. Low levels of genetic diversification between species could result in relatively fertile F 1 hybrids providing a bridge for further hybridization and thus introgression.…”
Section: Discussionmentioning
confidence: 87%
“…timidus , may nevertheless show marked mtDNA divergence, indicative of “good species”. He hypothesized that geographic, ecological, or behavioural isolation mechanisms may be driving speciation in the genus Lepus rather than genetic incompatibility, also in view of the very little chromosomal variation within the genus (e.g., Robinson et al[131,132], Azzaroli-Puccetti et al[133]). Later studies are not incongruent with this hypothesis (e.g., Alves et al[8], Liu et al[9], Wu et al[27], Melo-Ferreira et al[10,11], see also Thulin et al[7], and Robinson and Matthee[127]).…”
Section: Discussionmentioning
confidence: 99%
“…All species of Lepus that have been karyotyped have 2n = 48 (Robinson, Elder & Chapman, 1983b and references therein; Azzaroli Pucetti et al ., 1996; González & Cervantes, 1996; Lorenzo, Cervantes & Vargas, 2003), and differ only slightly in the amounts of pericentromeric heterochromatin. Karyotypic stability in this species may be a reflection of life history patterns, the recent radiation of species within the major evolutionary clades, genome stability and the species’ greater propensity for movement (and hence gene flow).…”
Section: Phylogenetic Arrangementsmentioning
confidence: 99%